2015
DOI: 10.1051/fruits/2015007
|View full text |Cite
|
Sign up to set email alerts
|

The photosynthesis inhibitor metamitron is a highly effective thinner for ‘Golden Delicious’ apple in a warm climate

Abstract: -Introduction. Small fruit size is a limiting factor in marketing apple (Malus × domestica). Several techniques have been used to improve fruit size, among them blossom and fruit thinning with plant growth regulators such as auxins and cytokinins to reduce crop load. Materials and methods. In the present study, carried out in 3 consecutive years (2012-2014), we evaluated the photosynthesis inhibitor metamitron (MM) as a thinner for 'Golden Delicious' apple. Results. MM applied once at 180-225 g ha −1 (150-190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
2
17
2
Order By: Relevance
“…Many authors have reported the day of maximum Brevis ® induced inhibition at between 2 and 6 days after application (Brunner, 2014;Rosa, 2016;Stern, 2015). Their results differ from the observations of this study, with maximum inhibition Qy(%) values observed 5-10 days after treatment.…”
contrasting
confidence: 98%
See 2 more Smart Citations
“…Many authors have reported the day of maximum Brevis ® induced inhibition at between 2 and 6 days after application (Brunner, 2014;Rosa, 2016;Stern, 2015). Their results differ from the observations of this study, with maximum inhibition Qy(%) values observed 5-10 days after treatment.…”
contrasting
confidence: 98%
“…Their results differ from the observations of this study, with maximum inhibition Qy(%) values observed 5-10 days after treatment. Moreover, Brevis ® reduced electron transport rates by up to 40%, with similar observations reported by , Stern (2014) and Stern (2015).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Single metamitron treatment improved average fruit size and fruit size distribution only when it significantly reduced the number of fruit, regardless of the application time, as similarly noted by Stern (2015). When metamitron application was repeated and it was mixed with other chemical thinners, increments in fruit size and share of the larger fruit in the total yield were regularly noted compared to the unthinned control treatment.…”
Section: Treatmentsupporting
confidence: 60%
“…Their leaf AA, TPC and osmolarity were also assessed, in order to identify a possible mechanism for the greater frost tolerance of ‘Ettinger’ than that of ‘Hass’. Measurements of physiological parameters following the controlled artificial frost treatments in the laboratory showed that detached ‘Ettinger’ branches had greater tolerance of the FHL treatment than ‘Hass’ branches, as their visible damage rate was lower and F v / F m rate, a reliable quantitative indicator of frost damage and other stress damage (Rizza et al ., 2001; Ehlert and Hincha, 2008; Stern, 2015), was significantly higher. These results are consistent with previously described frost-hardy characteristics of ‘Ettinger’ trees – descriptions mostly based on growers' observations over the years (data not shown).…”
Section: Discussionmentioning
confidence: 88%